ECOLEARNING TEMATIK SEBAGAI MODEL PEMBELAJARAN DI SEKOLAH DASAR (PIONIR: JURNAL PENDIDIKAN, 2022)
The use of learning models is one of the most important things in the process of implementing learning in elementary schools. The learning model applied in learning in elementary schools is the thematic ecolearning model. The purpose of this study was to determine the practical value of the thematic ecolearning model as a learning model in elementary schools. This type of research uses descriptive qualitative research. The research subjects were teachers and fourth grade students of SDN 9 Kuala Langsa. The results of this study describe the following; 1) Students are able to solve environmental problems in the learning process by using the thematic ecolearning model; 2) Learning problems that arise in everyday life make it easier for students to solve their problems; 3) Students are motivated in the learning process by using the thematic ecolearning model; and 4) Students are interested in learning to use the thematic ecolearning model.